Potensi Ekstrak Kulit Batang Bakau Minyak (Rhizophora apiculata) Sebagai Larvasida Terhadap Larva Aedes Aegypti - Dzakwan Cedri Ketierteu; Jhons Fatriyadi Suwandi; Putu Ristyaning Ayu Sangging; Hanna Mutiara (CV. Jasa Sukses Abadi, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease in humans which is transmitted by the Aedes aegypti mosquito as a vector which causes many cases of death. In Indonesia, the number of cases of dengue fever deaths will be 705 cases in 2021. Alternative natural insecticides are needed to avoid potential resistance to chemical insecticides. Rhizophora apiculata stem bark contains active compounds, namely saponins, flavonoids, alkaloids, and tannins which are larvicidal. The purpose of this study was to determine the larvicidal effectiveness of Rhizophora apiculata stem bark extract. This study used a laboratory experimental research design with a post test only control group design pattern. Divided into 6 groups, namely negative control, 0.045%, 0.09%, 0.18%, 0.36%, and positive control. Each group contained 25 larvae in 20 ml of Rhizophora apiculata stem bark extract solution with 4 repetitions. The data analysis used was univariate data analysis to find which concentration caused the highest death of Aedes aegypti larvae. From the research results, it was found that the average mortality of larvae from 4 repetitions at concentrations of 0.045%, 0.09%, 0.18%, and 0.36% were 68%, 97%, 99%, and 100% respectively.